ETHICAL POLITIC AND EMERGENCE OF INTELLECTUAL CLASS - Abdullah, Annzar (Paramita: Historical Studies Journal, 2017)
This study aimed to examine and analyze the relationship between the ethical and the birth of the educated classes in the Dutch East Indies (Indonesia) in the colonial period.  The research is qualitative by using methods and approach to historical analysis.  The methods and approach to historical analysis combined with interactive methods, interdisciplinary and inter-textual to gain an understanding of the diverse impulses and interactions that contributed to the birth of the educated classes in the Indian Dutch the colonial period.  The results showed that the policy of "ethical policy" in the liberal period in the Dutch East Indies (Indonesia) have an impact on the formation of the educated native Indonesia.  Through this policy the bumiputera can find the momentum to get an education in the West.  The intellectuals who were born from these intellectuals have paved the way for poles crucial as a public educator.  This means that they have to wake Dutch East Indies (Indonesia) from a long hibernation during this time.  The presence of intellectuals in public spaces contribute to the growth of national consciousness, which in turn form the collective consciousness as a nation-state. Penelitian ini bertujuan untuk mengkaji dan menganalisis hubungan antara etika dan kelahiran dari kelas terdidik di Hindia Belanda (Indonesia) pada masa kolonial. Penelitian kualitatif dengan menggunakan metode dan pendekatan untuk analisis sejarah. Metode dan pendekatan analisis historis dikombinasikan dengan metode interaktif, interdisipliner dan intertekstual untuk memperoleh pemahaman tentang impuls beragam dan interaksi yang berkontribusi terhadap lahirnya kelas terdidik di Belanda India masa kolonial. Hasil penelitian menunjukkan bahwa kebijakan "politik etis" pada periode liberal di Hindia Belanda (Indonesia) berdampak pada pembentukan asli Indonesia yang berpendidikan. Melalui kebijakan ini bumiputera dapat menemukan momentum untuk mendapatkan pendidikan di Barat. Para intelektual yang lahir dari para intelektual ini telah membuka jalan bagi kutub penting sebagai pendidik masyarakat. Ini berarti bahwa mereka harus bangun Hindia Belanda (Indonesia) dari tidur panjangnya selama ini. Kehadiran intelektual di ruang publik memberikan kontribusi pada pertumbuhan kesadaran nasional, yang pada gilirannya membentuk kesadaran kolektif sebagai sebuah negara-bangsa.